IMPROVING ENGLISH LEARNING FOR KINDERGARTEN STUDENTS THROUGH COMMMA APPLICATION IN NEW NORMAL ERA - Afita D. Prastiwi; Kinanti R. Hayati; Dwi S. Donoriyanto; Tranggono; Zinedine A. Sasmito (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
English is one of international languages for connecting and sharing knowledge throughout the world. As regulated in the national standards of early childhood education (PAUD), language is one of the measurement criteria in the early childhood education system. The aim of this research is to assist schools in improving human resources by providing training on English teaching methods with the Total Physical Response (TPR) method and English teaching applications with the android-based application called Comma. we collaborated with partners to design and create Comma application concept and system. The aim of this program is improving the quality of human resources in terms of teaching English for kindergarten students. The test results state that all operations can be performed on this Comma application which shows the system operated as expected or it can be said that the system testing is successful so that the Comma application is ready to be released and used by users who need this application to improve their English skills through the TPR method. With the Comma application, it can be used to improve understanding of the English language, especially in early childhood education and can be used as a good alternative in teaching English in the early childhood education environment.